Monitoring Analysis of Filling The Informed Consent of Blood Transfusion - Ruhana, Ati Rusyda; Pohan, Vivi Yosafianti; Hartiti, Tri (University of Muhammadiyah Semarang, 2021)
Informed consent is evidence of the accountability of health service providers in the hospital. it is carried out in every carrying out the procedure of actions that have the risk of causing disability or death. Incomplete documentation of patient informed consent can reduce the quality of hospital services. the implementation of informed consent documentation in hospitals often faces obstacles. this is due to the lack of human resources and the high workload available. This case study aims to determine the filling of informed consent documentation in the patient's blood transfusion. This study uses interviews, observation and document study by developing approaches to the nursing management function, organizing functions, personnel, direction, supervision, care management, logistics management, quality assurance programs and patient safety. The results showed that in one month there were 20 patients with blood transfusions, and 11 out of 20 patients did not have informed consent. The problem that arises is the incomplete documentation of medical records at the time of carrying out blood transfusions to patients. Supervision that is not optimal is the cause of this problem.